An approximate solution to the flow field on vegetated intertidal platforms: Applicability and limitations. Issue 8 (1st August 2014) - Van Oyen, T.; Carniello, L.; D'Alpaos, A.; Temmerman, S.; Troch, P.; Lanzoni, S.
Abstract Tidal wetland evolution is governed by interactions between topography, vegetation, and the flow field. Aiming to provide an appropriate hydrodynamic tool within a long‐term geomorphic model of vegetated wetlands, we describe an approximate procedure to model the depth‐averaged flow field on vegetated intertidal platforms. The procedure is tested by a qualitative comparison with laboratory experiments and quantitatively comparing with a numerical model, focusing on the influence of spatial variations in friction on the flow field. Overall, satisfactory comparisons are obtained. Nevertheless, some limitations of the approach are apparent. These are discussed in the light of the model assumptions. We analyze the impact of the observed limitations on the ability of the approximate solution to describe the morphodynamic evolution of the bed elevation. This is performed by evaluating the changes in the bed elevation after one tidal cycle on the intertidal platform based on flow velocities obtained with a numerical model and those of the simplified procedure. It is found that the bed evolution on the platform is reasonably described with the approximate solution, even though the accumulation of sediment is underestimated near the watershed divide by the approximate model. Taking into account the computationally economic character of the approximate procedure, the analysis indicates that the model provides a suitable tool to investigate the long‐term morphodynamic evolution of tidal wetlands.